KERAGAMAN DAN KEMIRIPAN SPESIES BURUNG PADA TIGA TIPE HABITAT DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS UNIVERSITAS LAMBUNG MANGKURAT (KHDTK ULM) - Satria Purbaya; Mochamad Arief Soendjoto; Suyanto Suyanto (Jurnal Sylva Scienteae, 2020)
There are no publications on bird diversity in the Forest Area for Special Purpose, Lambung Mangkurat University (KHDTK ULM). This study aimed to analyze the diversity and similarity of bird species in the secondary natural forest, the plantation forest, and shrubs in the KHDTK ULM. Data related to diurnal birds was collected in these three habitat types. Researchers walked slowly following the transects (footpaths, inspection paths) that were already in each habitat type and recorded the name of the species and the number of individuals observed within 25 m between 06.30 - 10.00 and 15.00 - 18.00 in three replications. The data was processed to obtain diversity index of bird species (Shannon-Wienner index) and similarity index of species, as well as protection and conservation status according to LHK Regulation No. 106 of 2018 and its conservation according to IUCN. Twenty-eight species or 17 bird families were found in the area. Three of them are protected and most are categorized as least concern. The habitat types with species diversity index from highest to lowest are plantation forest, shrubs, and secondary natural forest. Based on the similarity index, the highest similarity of bird species occurs between secondary natural forest and shrub, while the lowest is between secondary natural forest and plantation forest.Keywords: diversity; forest are; habitat type; similarity; special purpose